Driving Institutional Quality: Evaluating the Implementation of Internal Quality Assurance Models in Rural State Madrasahs - Nur Widiantoro (Al-Qalam Institue, 2026)
This study aims to evaluate how implementing an Internal Quality Assurance System (SPMI) contributes to improving institutional quality in a rural state madrasah. Educational quality disparities between urban and peripheral regions remain a persistent challenge, particularly for Islamic educational institutions that often face limitations in infrastructure, management capacity, and access to resources. Strengthening internal quality governance in madrasahs is therefore essential to ensure equitable and sustainable educational development. This research employs a qualitative descriptive case study conducted at a madrasah. Data were collected through participant observation, in-depth interviews with key informants, and documentation analysis, and analyzed using an interactive model of data reduction, data display, and conclusion verification. The findings reveal three major patterns. First, integrating a digital-based SPMI system improves transparency and enables real-time monitoring of institutional performance. Second, instructional leadership plays a crucial role in translating national curriculum policies into locally relevant pedagogical practices through mentoring and clinical supervision. Third, the madrasa demonstrates organizational responsiveness to students’ digital behavioral trends through structured digital literacy and ethical guidance programs. These findings contribute to the development of an adaptive quality management model for madrasahs and recommend strengthening digital governance and leadership capacity in similar educational institutions.